Molecular epidemiology of tuberculosis in London 1995–7 showing low rate of active transmission. Issue 7 (1st July 2002) - Maguire, H; Dale, J W; McHugh, T D; Butcher, P D; Gillespie, S H; Costetsos, A; Al-Ghusein, H; Holland, R; Dickens, A; Marston, L; Wilson, P; Pitman, R; et al.
Abstract : Background: Tuberculosis notification rates for London have risen dramatically in recent years. Molecular typing of Mycobacterium tuberculosis has contributed to our understanding of the epidemiology of tuberculosis throughout the world. This study aimed to assess the degree of recent transmission of M tuberculosis in London and subpopulations of the community with high rates of recent transmission. Methods: M tuberculosis isolates from all persons from Greater London diagnosed with culture positive tuberculosis between 1 July 1995 and 31 December 1997 were genetically fingerprinted using IS 6110 restriction fragment length polymorphism (RFLP) typing. A structured proforma was used during record review of cases of culture confirmed tuberculosis. Cluster analysis was performed and risk factors for clustering were examined in a univariate analysis followed by a logistic regression analysis with membership of a cluster as the outcome variable. Results: RFLP patterns were obtained for 2042 isolates with more than four copies of IS 6110 ; 463 (22.7%) belonged to 169 molecular clusters, which ranged in size from two (65% of clusters) to 12 persons. The estimated rate of recent transmission was 14.4%. Young age (0–19 years) (odds ratio (OR) 2.65, 95% confidence interval (CI) 1.59 to 4.44), birth in the UK (OR 1.55, 95% CI 1.04 to 2.03), black Caribbean ethnic group (OR 2.19, 95% CI 1.15 to 4.16), alcohol dependence (OR 2.33, 95% CI 1.46 to 3.72), and streptomycin resistance (OR 1.82, 95% CI 1.15 to 2.88) were independently associated with an increased risk of clustering. Conclusions: Tuberculosis in London is largely caused by reactivation or importation of infection by recent immigrants. Newly acquired infection is also common among people with recognised risk factors. Preventative interventions and early diagnosis of immigrants from areas with a high incidence of tuberculosis, together with thorough contact tracing and monitoring of treatment outcome among all cases of tuberculosis (especially in groups at higher risk of recent infection), remains most important.